Patient-Derived Extracellular Vesicles Proteins as New Biomarkers in Multiple Myeloma - A Real-World Study - Ferreira, Bruna Velosa (2022)
Funding Information: This research was funded by the Champalimaud Foundation; by the Fundação para a Ciência e Tecnologia – FCT (Research Grant PTDC/MEC-HEM/30315/2017) and by Sociedade Portuguesa de Hematologia -SPH (Initiation to Investigation Grant 2018).